Approaching the Theoretical Sodium Storage Capacity and Ultrahigh Rate of Layer‐Expanded MoS2 by Interfacial Engineering on N‐Doped Graphene. Issue 12 (8th February 2021) - Liang, Shichuan; Zhang, Su; Liu, Zheng; Feng, Jing; Jiang, Zimu; Shi, Mengjiao; Chen, Lan; Wei, Tong; Fan, Zhuangjun
Abstract: Molybdenum disulfide (MoS2 ) holds great potential for sodium storage due to its high theoretical capacity of 670 mAh g −1 . However, its theoretical capacity is hardly realized because of low conductivity, sluggish electrochemical kinetics, and unsatisfied structural stability. Herein, a polyaniline‐mediated interfacial engineering strategy for the growth of interlayer‐expanded MoS2 nanoflowers on N‐doped graphene "land" (E‐MoS2 /NG) using Mo7 O24 6− anions adsorbed on positively charged polyaniline as the "seeds" is reported. The strong interfacial interaction between MoS2 and graphene through MoN bonds as well as ultrathin interlayer‐expanded MoS2 can significantly improve the electrochemical kinetics and structural stability. As a result, E‐MoS2 /NG with a high MoS2 content of 90 wt% shows a high capacity (620 mAh g −1 at 0.1 A g −1 ), an ultrahigh rate capability (201 mAh g −1 at 50 A g −1 ), and outstanding cycle performance (390 mAh g −1 after 1000 cycles at 1 A g −1 ). Importantly, MoS2 in the composite approaches its theoretical capacity of 670 mAh g −1 . Furthermore, the assembled E‐MoS2 /NG//activated carbon sodium ion capacitor delivers high energy densities of 150 and 82 Wh kg −1 at 35 and 14 421 W kg −1, respectively, and a capacity retention of 78.1% after 1500 cycles at 10 A g −1, demonstrating great potential for practical application. Abstract : Interlayer‐expanded MoS2 nanoflowers are grown on N‐doped graphene "land" with a strong interfacial interaction through a novel polyaniline‐mediated interfacial engineering strategy. The composite shows an ultrahigh rate capability and a remarkable cycle stability for sodium storage, in which MoS2 (90 wt%) realizes its theoretical capacity because of the significantly improved interfacial charge‐transfer and ion diffusion kinetics.